Chromatin Remodeling Enzyme Snf2h Is Essential for Retinal Cell Proliferation and Photoreceptor Maintenance - Kuzelova, Andrea; Dupacova, Naoko; Antosova, Barbora; Sunny, Sweetu Susan; Kozmik, Zbynek; Paces, Jan; Skoultchi, Arthur I; Stopka, Tomas; Kozmik, Zbynek (Cells, 2023)
Chromatin remodeling complexes are required for many distinct nuclear processes such as transcription, DNA replication, and DNA repair. However, the contribution of these complexes to the development of complex tissues within an organism is poorly characterized. Imitation switch (ISWI) proteins are among the most evolutionarily conserved ATP-dependent chromatin remodeling factors and are represented by yeast Isw1/Isw2, and their vertebrate counterparts Snf2h (Smarca5) and Snf2l (Smarca1). In this study, we focused on the role of the Snf2h gene during the development of the mammalian retina. We show that Snf2h is expressed in both retinal progenitors and post-mitotic retinal cells. Using Snf2h conditional knockout mice (Snf2h cKO), we found that when Snf2h is deleted, the laminar structure of the adult retina is not retained, the overall thickness of the retina is significantly reduced compared with controls, and the outer nuclear layer (ONL) is completely missing. The depletion of Snf2h did not influence the ability of retinal progenitors to generate all the differentiated retinal cell types. Instead, the Snf2h function is critical for the proliferation of retinal progenitor cells. Cells lacking Snf2h have a defective S-phase, leading to the entire cell division process impairments. Although all retinal cell types appear to be specified in the absence of the Snf2h function, cell-cycle defects and concomitantly increased apoptosis in Snf2h cKO result in abnormal retina lamination, complete destruction of the photoreceptor layer, and consequently, a physiologically non-functional retina.
Keywords: Animals; proliferace buněk; Retina; Mice, Knockout; myši knockoutované; Chromatin; Cell Nucleus; Mice; Chromosomal Proteins, Non-Histone; adenosintrifosfatasy; myši; buněčné jádro; restrukturace chromatinu; chromatin; Cell Proliferation; chromozomální proteiny, nehistonové; retina; zvířata; Adenosine Triphosphatases; Chromatin Assembly and Disassembly